DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION LEARNING MATERIALS BASED ON HIGHER ORDER THINKING SKILLS (HOTS) TO IMPROVE STUDENTS’ CRITICAL THINKING SKILLS - Hasanah, Ushie Uswatun; Suleman, Muh. Asharif; Idayanti, Zulfi; Rachmat, Muh Zacky Fadhil (EDU SOCIETY: JURNAL PENDIDIKAN, ILMU SOSIAL DAN PENGABDIAN KEPADA MASYARAKAT, 2026)
This study focuses on the development of Higher Order Thinking Skills (HOTS)-based Islamic Education (PAI) materials at SMA Negeri 15 Garut, aimed at enhancing students' critical thinking skills. HOTS-based learning is essential in the Society 5.0 era, which requires analytical, evaluative, and creative skills, as well as students' ability to internalize religious values in an applied manner. The research method used is classroom action research with a qualitative approach, involving observation, interviews, and documentation to analyze students' critical thinking skills. The study results show that HOTS-based materials are able to increase students' active engagement in class and encourage them to critically analyze and evaluate religious teachings. Students also demonstrate improvements in learning independence and metacognitive awareness, which play an important role in developing their life skills. These findings contribute significantly to the development of a HOTS-based PAI curriculum, which is expected to shape a generation with character and competitiveness in the future. This study recommends the broader implementation of HOTS across various educational levels and enhancing teachers' capacity to develop HOTS-based materials.